Kepentingan Indonesia Terhadap Ekspresi Budaya Tradisional Dalam Sumber Hukum Internasional Mengenai Hak Kekayaan Intelektual - Clara Ignatia Tobing; Jantarda Mauli Hutagalung (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The Regime of Genetic Resources, Traditional Knowledge and Traditional Cultural Expressions (SDGPTEBT) is a different regime from the existing regime of intellectual property rights. The WIPO negotiations on SDGPTEBT were held in order to discuss the protection of the SDGPTEBT at the international level. One of the problems that emerged from these negotiations was the gap between developed and developing countries regarding the final form of the outcome of the negotiations. There is still no clarity regarding the status of the